Effects of a Midwifery-Led Labor Management Program on Duration of Second Stage of Labor, Degree of Perineal Tear, and Childbirth Comfort in Primiparous Women - Srisun, Tiwa; Sangin, Siriwan; Chuahorm, Usa (Journal of Thailand Nursing and Midwifery Council, 2023)
Introduction: The second stage of labor is a critical period for ensuring the safety of both the mother and baby. Therefore, the quality of nursing care during this stage is of utmost importance, and it is essential that the nurse or midwife attending to the mother is highly attentive and competent. Objective: To investigate effects of a midwifery-led labor management program on the duration of second stage of labor, degree of perineal tear, and childbirth comfort among primiparous women. Design: Two-group posttest only experimental design Methodology: Participants were 50 primiparous women who presented to the labor room of a tertiary hospital in Nakhon Pathom province between April to September 2021. The participants were randomly assigned to either an experimental group (n = 25) or a control group (n = 25). The experimental group received the midwifery-led labor management program in addition to usual nursing care, which included education during the first stage of labor, a flexible sacrum position, spontaneous pushing, continuous support, and a two-step head-to-body delivery during the second stage of labor. The control group received usual nursing care only. Personal and obstetric data were collected using a record form, and a childbirth comfort questionnaire was administered, which had a content validity index of 1 and a reliability of .81. Data were analyzed using descriptive statistics, Independent t-test and Chi-square test. Results: Results revealed that the experimental group had a significantly shorter duration of second stage of labor, a lower degree of perineal tear and higher childbirth comfort than the control group (t = - 4.444, p < .001; Corrected Chi-square = 17.469, p < .001; t = 3.402, p < .001, respectively). Recommendation: Based on the study’s findings, it is recommended that midwives should utilize this midwifery-led labor management program when caring for laboring mothers in the delivery room